2022
DOI: 10.1002/jmri.28422
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of18F‐FDG PET/MRIfor Pleural Invasion in Solid and Subsolid Lung Adenocarcinomas Smaller Than 3 cm

Abstract: BackgroundPositron emission tomography (PET)/MRI combines the characteristics of metabolism imaging and high soft tissue resolution, and could provide high diagnostic efficacy for assessment of pleural invasion (PI) of lung cancer.PurposeTo investigate the application of 18F‐fluorodeoxyglucose (FDG) PET/MRI for predicting PI of lung cancer with the maximum diameter ≤3 cm.Study TypeProspective.PopulationA total of 44 patients with non‐small cell lung cancer (NSCLC), age from 39 to 79 years old, including 19 (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Zhang et al. ( 38 ) confirmed the effectiveness of 18 F-FDG PET/MRI radiomics in forecasting pleural invasion in lung adenocarcinomas smaller than 3 cm. These studies showed that PET-related radiomics was highly effective in predicting lung cancer stage and metastasis of whole body.…”
Section: Progress In the Application Of Pet-related Radiomics In Lung...mentioning
confidence: 90%
“…Zhang et al. ( 38 ) confirmed the effectiveness of 18 F-FDG PET/MRI radiomics in forecasting pleural invasion in lung adenocarcinomas smaller than 3 cm. These studies showed that PET-related radiomics was highly effective in predicting lung cancer stage and metastasis of whole body.…”
Section: Progress In the Application Of Pet-related Radiomics In Lung...mentioning
confidence: 90%
“…Elevated uptake of 18F-FDG is correlated with increased tumor invasiveness, which is also linked to VPI [ 14 , 16 ]. Zhang et al [ 17 ] observed that PET-CT, which provides both structural and functional information, is relatively intuitive and easy to interpret, making it a more suitable approach than CT imaging. Our study also revealed a significant correlation between SUVmax and VPI through multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Improved anatomic registration with PET secondary to simultaneous image acquisition is now a reality with the advent of simultaneous PET‐MR imaging scanners. In this article by Zhang et al, 2 the authors investigated 18 F‐FDG PET/MRI for predicting PI of lung adenocarcinoma ≤3 cm.…”
mentioning
confidence: 99%
“…Following its introduction in 2011, 4 the clinical utility of hybrid PET/MRI still holds a potential area of research in which organs and/or diseases it is preferable over PET/CT. This article 2 elucidates the role of PET/MRI in pleural invasion of lung adenocarcinomas.…”
mentioning
confidence: 99%